2018
DOI: 10.1016/j.addbeh.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and cessation-related differences between tobacco-marijuana co-users and single product users in a college student population

Abstract: Limited research has examined psychosocial factors that differ among cigarette users, marijuana users, and co-users and influence their cessation efforts. We examined: 1) sociodemographic, mental health, and other substance use in relation to user category; and 2) associations among these factors in relation to recent quit attempts and readiness to quit among single product versus co-users. We used a cross-sectional design to study college students aged 18-25 from seven Georgia campuses, focusing on the 721 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
1
7
0
3
Order By: Relevance
“…This is among the first studies in adult cannabis-tobacco cousers to explore quitting intentions and interest, as well as selfreported drug substitution. Quit interest and confidence in quitting was similar to previous studies that have been conducted among young adult co-users (Masters et al, 2018;Ramo et al, 2014). Important findings from the current study include: (a) while nearly all of the sample of co-users were interested in and had attempted to quit smoking cigarettes at least once, a much smaller proportion were interested in or had ever tried to quit using cannabis, and (b) approximately 50 -60% of participants perceived increases in their use of the substance they were not trying to quit (cannabis or cigarettes, respectively) during past quit attempts.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is among the first studies in adult cannabis-tobacco cousers to explore quitting intentions and interest, as well as selfreported drug substitution. Quit interest and confidence in quitting was similar to previous studies that have been conducted among young adult co-users (Masters et al, 2018;Ramo et al, 2014). Important findings from the current study include: (a) while nearly all of the sample of co-users were interested in and had attempted to quit smoking cigarettes at least once, a much smaller proportion were interested in or had ever tried to quit using cannabis, and (b) approximately 50 -60% of participants perceived increases in their use of the substance they were not trying to quit (cannabis or cigarettes, respectively) during past quit attempts.…”
Section: Discussionsupporting
confidence: 87%
“…While preliminary work has been conducted on the evaluation of interventions to address cannabis and tobacco co-use (Becker, Haug, Sullivan, & Schaub, 2014; Beckham et al, 2018; Hill et al, 2013; Lee et al, 2015), little is known regarding quit interest and treatment preferences among co-users. Among young adults (ages 18–25), previous studies have found that the desire to quit smoking cigarettes is greater than for cannabis, the perceived importance of quitting is greater for cigarettes, but confidence in quitting smoking cigarettes is lower (Masters, Haardorfer, Windle, & Berg, 2018; Ramo, Delucchi, Liu, Hall, & Prochaska, 2014). Extending this work to adult co-users is an important contribution to the treatment literature.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, youth who reported coadministration and sequential use, either alone or in combination, also reported poorer outcomes compared to youth using only one product or using both products independently. There is some literature on psychosocial and physical health correlates of co-use in young adults (Masters, Haardörfer, Windle, & Berg, 2018; Ramo et al, 2012); however, further longitudinal research is needed to examine how outcomes may differ across types of co-use over time and to identify mechanisms underlying these differences. For example, differences across types of co-use may be due to the manner in which cannabis and tobacco/nicotine are co-used, characteristics of the person who chooses to co-use in a particular way, or other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Persons who smoke cigarettes are significantly more likely to report cannabis use and CUDs8 19 25 26 and, conversely, persons who use cannabis and have CUDs are more likely to report cigarette smoking 6 24 26–28. The use of cannabis and cigarettes together is associated with a range of adverse physical, psychological, cognitive and social consequences as well as an increased likelihood of CUDs, less confidence in quitting and readiness to quit cannabis, and less success with abstinence from cannabis 29–33. Over the past decade, there has been an increase in the use of cannabis among cigarette smokers19 and prevalence of cigarettes and cannabis co-use,34 suggesting that the negative consequences of cigarette–cannabis co-use may also become more prevalent over time.…”
Section: Introductionmentioning
confidence: 99%